EXPLORING THE PERCEPTION OF MUMBAI BASED CHARTERED ACCOUNTANTS TOWARDS CLOUD COMPUTING IN PRACTICE - Dr. Ganatra Kashyap A. (International Educational Journal of Science and Engineering, 2025)
Cloud computing has emerged as a transformative force in the accounting profession, offering enhanced data accessibility, cost efficiency, and operational flexibility. However, its adoption and practical implementation vary across professional communities. This study seeks to explore the perception of Mumbai-based Chartered Accountants (CAs) regarding the use of cloud computing in their accounting practices. Specifically, the research investigates how demographic factors such as age, experience, gender, and type of practice influence their perception and acceptance of cloud-based solutions. A structured questionnaire was administered to 167 Chartered Accountants operating in Mumbai. The study employs quantitative methods to analyse perceptions, including ease of use, security concerns, efficiency, and overall benefits of cloud computing in accounting. Findings are expected to provide insights into the prevailing mind-set among professionals and identify gaps that may hinder cloud adoption in the accounting sector. The results aim to support policymakers, accounting bodies, and software vendors in designing more tailored training, policy, and adoption strategies.